Influence of overweight and obesity on perinatal outcomes in assisted reproduction: a retrospective cohort study - Victoria Campos Dornelles; Marta Ribeiro Hentschke; Mariangela Badalotti; Isadora Badalotti-Teloken; Vanessa Devens Trindade; Bibiana Cunegatto; Natália Fontoura de Vasconcelos; Alvaro Petracco; Bartira Ercília Pinheiro da Costa; Alexandre Vontobel Padoin (BMC, 2022)
Abstract Background In spontaneous pregnancies, maternal weight and gestational diabetes are independent risk factors for macrosomia and large-for-gestational-age newborns. Furthermore, maternal body mass index (BMI) of ≥25 kg/m2 is associated with worse neonatal vitality, classified as an Apgar score of < 7 at the fifth minute of life. However, few studies have evaluated the influence of BMI on perinatal outcomes in pregnancies resulting from assisted reproduction. Therefore, this study aimed to analyze whether the perinatal outcomes of assisted reproduction are influenced by BMI. Methods This was a retrospective cohort study performed at a reproductive medicine center. Patients undergoing assisted reproduction (2013-2020) were divided into three groups according to their BMI (kg/m2): group 1, < 25; group 2, 25-29.9, and group 3, ≥30. In total, 1753 in vitro fertilization embryo transfer cycles were analyzed. Data were expressed as mean ± standard deviation or frequency (%). The analysis of variance and chi-square test were performed for comparison. To determine the participants and number of cycles for these analyses, generalized estimating equations were used, considering p < 0.05. Results In groups 1, 2, and 3, the rates of live birth were 33.5, 32.3, and 29.9% (p = 0.668); preeclampsia were 2.9, 6.1, and 6.3% (p = 0.268); small-for-gestational-age newborns were 23, 23.2, and 21.7% (p = 0.965); macrosomia were 1.9, 0.9, and 2.7% (p = 0.708); Apgar score > 7 at the fifth minute were 97.6, 98.2, and 100% (p = 0.616); and preterm birth were 29.6, 30.1, and 35.1% (p = 0.970), respectively. Conclusions In conclusion, although the three groups had similar perinatal outcomes in this study, the study population was too small for conclusive results. The higher the BMI, the lower the chances of clinically relevant LBR and the higher the chances of premature labor and preeclampsia.